5‐5: Distinguished Paper/Late-News Paper: The First 9.1‐inch Stretchable AMOLED Display based on LTPS Technology. Issue 1 (May 2017) - Hong, Jong-Ho; Shin, Jae Min; Kim, Gun Mo; Joo, Hyejin; Park, Gyung Soon; Hwang, In Bom; Kim, Min Woo; Park, Won-Sang; Chu, Hye Yong; Kim, Sungchul
Abstract : In this work, we report a freeform shaped display based on LTPS AMOLED technology. Our AMOLED, developed with a unique pixel structure, can withstand in various desired shapes featuring its stretchable property with no degradation of image quality and device characteristics. We demonstrated unprecedented convex/concave shape of the 9.1‐inch AMOLED display by low‐temperature thermoforming process. Our approach would have great potential in creating a new platform for the future display applications with design freedom such as automotive and wearable electronics.